2015
DOI: 10.1111/iwj.12484
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C promotes wound healing through novel pleiotropic mechanisms

Abstract: Vitamin C (VitC) or ascorbic acid (AscA), a cofactor for collagen synthesis and a primary antioxidant, is rapidly consumed post-wounding. Parenteral VitC administration suppresses pro-inflammatory responses while promoting anti-inflammatory and pro-resolution effects in human/murine sepsis. We hypothesised that VitC could promote wound healing by altering the inflammatory, proliferative and remodelling phases of wound healing. Mice unable to synthesise VitC (Gulo(-/-) ) were used in this study. VitC was provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
123
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(131 citation statements)
references
References 50 publications
(63 reference statements)
3
123
0
5
Order By: Relevance
“…In contrast, intravenous administration of vitamin C may have yielded plasma vitamin C concentrations approximately 250-times higher than that of patients receiving vitamin C supplements orally. 18 In this study, the effects on wound healing became visible by day 14 postsurgery. The surgical procedure conducted in patients from group D was less invasive than the procedure performed in the other groups, which suggests that group D plasma vitamin C levels may have been affected less by the surgery.…”
Section: Effects Of Vitamin C On Postoperative Painmentioning
confidence: 62%
See 3 more Smart Citations
“…In contrast, intravenous administration of vitamin C may have yielded plasma vitamin C concentrations approximately 250-times higher than that of patients receiving vitamin C supplements orally. 18 In this study, the effects on wound healing became visible by day 14 postsurgery. The surgical procedure conducted in patients from group D was less invasive than the procedure performed in the other groups, which suggests that group D plasma vitamin C levels may have been affected less by the surgery.…”
Section: Effects Of Vitamin C On Postoperative Painmentioning
confidence: 62%
“…25,26 The healing process for oral wounds closely mimics the wound healing of other connective tissues in the body. 24,28 Previously, Mohammed and colleagues 18 showed that vitamin C could promote wound healing through a variety of mechanisms. 24,28 Previously, Mohammed and colleagues 18 showed that vitamin C could promote wound healing through a variety of mechanisms.…”
Section: Effects Of Vitamin C On Postoperative Painmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the vascular effects outlined above, it is well established that AA levels in the scurvy range (ie, below 10 micromolar), as in our cohort may be associated with wound healing impairment . Repletion of ascorbate in these settings, accelerates wound healing and may result in attenuation of oral and gastrointestinal mucosal injury and subsequently diminished release of inflammatory cytokines (IL‐1 and TNF‐α), with up‐regulation of mediators of wound healing (TGF‐β and vascular endothelial growth factor) in animal models . Similar effect has been demonstrated in a swine model of multiple injuries where AA administration attenuated the organ injury and with relative reduction in the production of TNF, IL‐1, IL‐8, tissue factor, and plasminogen activation inhibitor‐1 .…”
Section: Discussionmentioning
confidence: 72%